Prevalence of lower urinary tract symptoms and overactive bladder in men and women over 18 years old: The Colombian overactive bladder and lower urinary tract symptoms (COBaLT) study. Issue 1 (24th September 2018) - Plata, Mauricio; Bravo‐Balado, Alejandra; Robledo, Daniela; Trujillo, Carlos G.; Caicedo, Juan I.; Cataño, Juan G.; Arenas, Julián; Rondón, Martín; Londoño, Darío
Abstract : Aims: To estimate the prevalence of LUTS and overactive bladder (OAB) in the Colombian population. Methods: A cross‐sectional, population‐based study was conducted in men and women ≥18 years using directed interviews and self‐administered questionnaires in five main cities in Colombia. A sample size of 1054 subjects was estimated (prevalence of LUTS/OAB 15%, CI 95%, statistical power 80%, precision 3%). We used a multi‐stage probabilistic sampling technique to randomly select individuals in the community, stratified by socioeconomic status, gender, and age. We used the 2002 ICS and 2010 IUGA/ICS definitions as well as validated questionnaires in Spanish. Descriptive statistics were employed. Results: A total of 1060 participants were included. Mean age was 42 (range 18‐89) years. The prevalence of at least one LUTS was 84%, while overactive bladder was reported by 31.8% participants. Among individuals with at least one LUTS, 13.2% would feel "mostly unsatisfied, " "unhappy, " or "terrible" to spend the rest of their lives with their current urinary condition. Nocturia was the most prevalent LUTS (55.3%), followed by urgency (46.4%) and frequency (45.8%). Urge, stress, and mixed urinary incontinence were reported by 15.3%, 8.6%, and 7% of participants, respectively. Conclusions: LUTS are highly prevalent in the Colombian population and severely affect quality of life. This is the first study conducted in Colombia and Latin America focused on evaluating LUTS in men and women of all age groups of interest using a multi‐stage probabilistic sampling technique. These results may have a significant influence on health decision‐making and assessment of future therapies.